Lessons from Fort Apache : beyond language endangerment and maintenance - Nevins, M. Eleanor (Chichester, West Sussex : Wiley Blackwell, 2013)
"This incisive ethnographic analysis of indigenous language documentation, maintenance, and revitalization focuses on linguistic heritage issues on the Native American reservation at Fort Apache and explores the broader social, political and religious influences on changing language practices in indigenous communities. Offers a focused ethnographic analysis of an indigenous community that also explores global issues of language endangerment and maintenance and their socio-historical contexts"--Product Information.
Introduction -- Indigenous languages and the mediation of communities -- Learning to listen -- They live in Lonesome Dove -- Stories in the moment of encounter -- What no Coyote story means -- "Some 'no no' and some 'yes'" -- Sustainability -- Appendix A: Lawrence Mithlo -- Appendix B: Eva Lupe on her early life -- Index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Apache Indians -- Arizona -- Fort Apache Indian Reservations -- Languages; Apache Indians -- Arizona -- San Carlos Indian Reservation -- Languages; Endangered languages; Language maintenance; Ethnology; Anthropological linguistics; Apache Indians -- Social life and customs; HISTORY -- United States -- State & Local -- General; Electronic books